Public Governance in Accountability of Village Enterprise (BUMDes) Management: a Stakeholders Perspective - Denok Kurniasih; Shadu S. Wijaya; Paulus Israwan Setyoko (Iapa Proceedings Conference, 2018)
This paper discusses the imbalance of the role of stakeholders in the accountability of village enterprise management. One of the stakeholders dominates, this has hampered corporate actions based on public governance on the accountability of BUMDes management. Accountability is only carried out as a form of procedural accountability to the village government and district government. Even though there is a horizontal accountability mechanism to the public, it does not work effectively. One of the reasons for the accountability failure of BUMDes management is the unclear role and responsibility of stakeholders in managing BUMDes. Rural Communities, Representative Institutions (Badan Permusyawaratan Desa), Private Sector, and the ohter Village Institutions do not have proportional roles and responsibilities in the accountability mechanism for BUMDes management. It means the capacity of stakeholders in the accountability process of BUMDes management is relatively low. Even though the capacity of stakeholders is important to strengthen the accountability of BUMDes management, because all stakeholders can monitor and evaluate the management of BUMDes, so that the dominance of the Headman and BUMDes’s manager can be controlled. Therefore, in overcoming the vacancy in the role of stakeholders, this research proposes the need to create an accountability mechanism based on public governance, where all stakeholders will interact with each other with the aim of influencing the results of public policy. They interact with each other in the management of public organizations to fulfill various interests of the community. To integrate the role of stakeholders in the accountability of BUMDes management it is advisable to use an information system that can bring together all stakeholders in managing a BUMDes. The information system can be used to strengthen the accountability model based on public governance on the management of BUMDes.